PENGEMBANGAN BUDAYA MADRASAH UNTUK PENINGKATAN KEDISIPLINAN SISWA MELALUI SISTEM POIN DI MADRASAH ALIYAH (MA) RAUDLATUL ULUM PUTRI GANJARAN GONDANGLEGI MALANG - Ilyatus Sholihah (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to identify and describe 1) the concept of madrasa culture developed to improve student discipline through a point system, 2) implementation of madrasa culture development to improve student discipline through a point system, 3) Implications of developing madrasa culture for improving student discipline through a point system. at the MA Raudlatul Ulum Putri Ganjaran Gondanglegi Malang. This study uses a descriptive approach. Data collection techniques by means of observation, in-depth interviews and documentation studies. Data analysis consists of data reduction, data presentation, and drawing conclusions. In this study, the research subjects were the principal, deputy head of student affairs, and several students. The results showed that the development of madrasa culture to improve student discipline through the points system of MA Raudlatul Ulum Putri Ganjaran Gondanglegi Malang, namely: 1) The concept of madrasa culture developed to improve student discipline through the point system at MA Raudlatul Ulum Putri Ganjaran Gondanglegi Malang, namely: religious and in the field of discipline 2) Implementation of madrasa culture development to improve student discipline through the implementation of a point system that is applied in madrasa rules, an examination system for student tardiness and application of fingerprints 3) Implications of developing madrasa culture for increasing student discipline through a point system in the form of very significant changes in improving student discipline. That is, if the quality of madrasa culture is improved, the quality of student discipline will also increase.